Probiotic Potential Analysis and Safety Evaluation of Enterococcus durans A8-1 Isolated From a Healthy Chinese Infant - Zhou, Yi; Shi, Lu; Wang, Juan; Yuan, Jia; Liu, Jin; Liu, Lijuan; Da, Rong; Cheng, Yue; Han, Bei (Frontiers in Microbiology, 2021)
To evaluate the probiotic characteristics and safety of Enterococcus durans isolate A8-1 from a fecal sample of a healthy Chinese infant, we determined the tolerance to low pH, survival in bile salts and NaCl, adhesion ability, biofilm formation, antimicrobial activity, toxin gene distribution, hemolysis, gelatinase activity, antibiotic resistance, and virulence to Galleria mellonella and interpreted the characters by genome resequencing. Phenotypically, E. durans A8-1 survived at pH 5.0 in 7.0% NaCl and 3% bile salt under aerobic and anaerobic condition. The bacterium had higher adhesion ability toward mucin, collagen, and Bovine Serum Albumin (BSA) in vitro and showed high hydrophobicity (79.2% in chloroform, 49.2% in xylene), auto-aggregation activity (51.7%), and could co-aggregate (66.2%) with Salmonella typhimurium. It had adhesion capability to intestinal epithelial Caco-2 cells (38.74%) with moderate biofilm production and antimicrobial activity against several Gram-positive pathogenic bacteria. A8-1 can antagonize the adhesion of S. typhimurium ATCC14028 on Caco-2 cells to protect the integrity of the cell membrane by detection of lactate dehydrogenase (LDH) and AKP activities. A8-1 also helps the cell relieve the inflammation induced by lipopolysaccharide by reducing the expression of cytokine IL-8 (P = 0.002) and TNF-α (P > 0.05), and increasing the IL-10 (P < 0.001). For the safety evaluation, A8-1 showed no hemolytic activity, no gelatinase activity, and had only asa1 positive in the seven detected virulence genes in polymerase chain reaction (PCR), whereas it was not predicted in the genome sequence. It was susceptible to benzylpenicillin, ampicillin, ciprofloxacin, levofloxacin, moxifloxacin, tigecycline, nitrofurantoin, linezolid, vancomycin, erythromycin, and quinupristin/dalofopine except clindamycin, which was verified by the predicted lasA, lmrB, lmrC, and lmrD genes contributing to the clindamycin resistance. The virulence test of G. mellonella showed that it had toxicity lower than 10% at 1 × 107 CFU. According to the results of these evaluated attributes, E. durans strain A8-1 could be a promising probiotic candidate for applications.